Marginal Zone B-Cells, a Gatekeeper of Innate Immunity - ZOUALI, Moncef; RICHARD, Yolande (Frontiers in Immunology, 2011)
To maintain the integrity of an organism constantly challenged by pathogens, the immune system is endowed with a variety of cell types. B-lymphocytes were initially thought to only play a role in the adaptative branch of immunity. However, a number of converging observations revealed that two B-cell subsets, marginal zone (MZ) and B1 cells, exhibit unique developmental and functional characteristics, and can contribute to innate immune responses. In addition to their capacity to mount local antibody response against type 2 T-independent (TI-2) antigens, MZ B-cells can participate to T-dependent (TD) immune response through the capture and import of blood-borne antigens to follicular areas of the spleen. Here, we discuss the multiple roles of MZ B-cells in rodents and primates. We also summarize studies —performed in transgenic mice expressing fully human antibodies on their B-cells and macaques whose infection with Simian Immunodeficiency Virus (SIV) represents a suitable model for HIV-1 infection in humans— showing that infectious agents have developed strategies to subvert MZ B-cell functions. In these two experimental models, we observed that two microbial superantigens for B-cells (protein A from Staphylococcus aureus and protein L from Peptostreptococcus magnus) as well as inactivated AT-2 virions of HIV-1 and infectious SIV preferentially deplete innate-like B-cells —MZ B-cells and/or B1 B-cells— with different consequences on TI and TD antibody responses. These data revealed that viruses and bacteria have developed strategies to deplete innate-like B-cells during the acute phase of infection and to impair the antibody response. Unraveling the intimate mechanisms responsible for targeting MZ B-cells in humans will be important for understanding disease pathogenesis and for designing novel vaccine strategies.